1982
DOI: 10.1007/bf01405845
|View full text |Cite
|
Sign up to set email alerts
|

Subacute myelopathy as the presenting manifestation of sarcoidosis

Abstract: We studied a patient with progressive myelopathy, in whom systemic sarcoidosis was discovered. Involvement of other organs was asymptomatic. The myelopathy considerably improved after corticosteroid therapy. Spinal cord involvement in sarcoidosis is very uncommon, and its occurrence as a presenting manifestation is even rarer. Prompt recognition is emphasized, because it is a treatable condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…Although the clinical phenotype varies depending on the geographical region and ethnicity, both sexes and all ethnicities and ages are affected globally. In comparison to that observed in Western countries, Japanese sarcoidosis has been 2042 ment is an extremely rare manifestation of sarcoidosis, occurring in 0.34% of cases of systemic sarcoidosis (3). In Japan, the incidence of nervous system involvement has been reported to be 7.2% in patients with sarcoidosis (1); therefore, making the initial diagnosis of spinal cord sarcoidosis is challenging due to the rarity of the disease, particularly when systemic findings of the disease are unclear (4).…”
Section: Introductionsupporting
confidence: 41%
“…Although the clinical phenotype varies depending on the geographical region and ethnicity, both sexes and all ethnicities and ages are affected globally. In comparison to that observed in Western countries, Japanese sarcoidosis has been 2042 ment is an extremely rare manifestation of sarcoidosis, occurring in 0.34% of cases of systemic sarcoidosis (3). In Japan, the incidence of nervous system involvement has been reported to be 7.2% in patients with sarcoidosis (1); therefore, making the initial diagnosis of spinal cord sarcoidosis is challenging due to the rarity of the disease, particularly when systemic findings of the disease are unclear (4).…”
Section: Introductionsupporting
confidence: 41%
“…However, as shown in this study, the effects of laminoplasty are not predictable in the treatment of spinal cord sarcoidosis even when patients have spondylotic changes and/or a constitutionally narrowing cervical spinal canal. It has been reported that a long interval from the onset of disease to the initiation of corticosteroid therapy contributes to poor functional recovery [1]; however, poor results were achieved in all our three patients even with the rapid administration of corticosteroid therapy. Thus, laminoplasty is not an effective intervention for the treatment of spinal cord sarcoidosis with or without spondylotic changes.…”
Section: Discussionmentioning
confidence: 52%
“…About 6-8% of cases with central nervous system involvement show spinal cord lesions [10,23]. Spinal cord involvement is rare, occurring in only 0.3-0.4% of patients with systemic sarcoidosis [1,26]. Thus, intramedullary neurosarcoidosis is a rare neurological manifestation, especially as an initial presentation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord involvement is extremely rare, occurring in only 0.3-0.4% of patients with systemic sarcoidosis [9][10][11] . Moreover, most spinal sarcoid lesions are intramedullary, only a few cases of extramedullary sarcoid lesions have been reported [12][13][14][15] .…”
mentioning
confidence: 44%